The Intention to Buy Halal Skincare for Men: A Case Study on Kahf Face Wash Product - Kurniastuti, Amelia; Wahyudi, Lilik (Journal of Organizational and Human Resource Development Strategies, 2025)
This study aims to determine the effect of perceived value, perceived risk, brand image, halal certification, and religiosity on beliefs, attitudes, halal awareness, and purchase intentions of halal products. Especially the Kahf brand face wash. The research population is those who are included in the category of Muslim men with an age range of 15-40 years. Its coverage area covers many cities in Indonesia. The analytical test method uses Structural Equation Modeling or SEM with SmartPLS 3. The samples studied were 284 respondents and were taken using purposive sampling techniques. The results of this study found that 8 out of 11 hypotheses were accepted. The accepted hypotheses include the influence of perception on trust, brand image on trust, religiosity on attitudes, halal certification on halal awareness, trust on purchase intentions, trust on attitudes, halal awareness on attitudes, and attitudes on purchase intentions. While the other 3 hypotheses, namely the effect of risk perception on trust, brand image on attitudes, and halal awareness on purchase intention, were found to have no significant effect, or in other words rejected.